Factors predicting outcome after pulmonary endarterectomy. - Cécile Tromeur; Xavier Jaïs; Olaf Mercier; Francis Couturaud; David Montani; Laurent Savale; Mitja Jevnikar; Jason Weatherald; Olivier Sitbon; Florence Parent; Dominique Fabre; Sacha Mussot; et al. (PLoS ONE)
Objective Few studies have reported predictive factors of outcome after pulmonary endarterectomy (PEA) in chronic thromboembolic pulmonary hypertension. The purpose of this study was to determine factors influencing mortality and predictors of hemodynamic improvement after PEA. Methods A total of 383 consecutive patients who underwent PEA between January 2005 and December 2009 were retrospectively reviewed. Among them, 150 were fully reevaluated 7.5±1 months after PEA by NYHA class, 6-minute walk distance (6MWD), percentage of predicted carbon monoxide transfer factor (TLCO) and right heart catheterisation. Results Mortality rates at 1 month, 1 year and 3 years were 2.8%, 6.9% and 7.5%, respectively. Preoperative pulmonary vascular resistance (PVR) independently predicted 1-month, 1- and 3-year mortality and age predicted mortality at 1 year and 3 years. Significant improvement in NYHA class and 6MWD were observed and PVR decreased from 773±353 to 307±221 dyn.sec.cm-5 (p<0.001). In 96 patients (64%), PVR decreased by at least 50% and/or was reduced to lower than 250 dyn.sec.cm-5. Preoperative cardiac output (CO) and TLCO predicted hemodynamic improvement. Conclusion PEA is associated with an excellent long-term survival and a marked improvement in clinical status and hemodynamics. Some preoperative factors including PVR, CO and TLCO can predict postoperative outcomes.